Evaluasi Proses Implementasi Kebijakan Program UHC (Universal Health Coverage) di Semarang - Delila Nisnoni; Sulistyowati . (Journal of Politic and Government Studies, 2020)
Health insurance is a government health services program. Tujuan adanyajaminan kesehatan adalah sebagai upaya menjaga diri demi kondisi kesehatan.Because Jaminan Kesehatan Nasional (JKN) Part of the Sistem Jaminan SosialNasional (SJSN) Conducted by the use of mandatory social health insurancemechanisms. Have a programme policy UHC (Univeral Health Coverage) The healthprogram implemented by the central government to improve public health, Becauseof the difficult coverage is known by the central government, local governments asrepresentatives of the central government can continue to reach the scope ofmembership to the regional level. This is the case in the city of Semarang, SemarangCity government initiating a program as a form of health insurance for the citizens ofthe Community, For the purpose of obtaining free medication services known asProgram UHC (Universal Health Coverage) By registering the residents ofSemarang as Penerima Bantuan Iuran (PBI) BPJS Kesehatan For residentswho have not been registered as a health insurance participant, unable to pay dues,delinquent.The research method that the authors use is qualitative deskiptif using thetheory of George C Edward III which focuses on the important variables on thesuccess of the program implementation, Communication, resources, disposition,bureaucratic structure and supported with triangulation theory to strengthen data.And identifying the driving factor and barriers of society in implementing theprogram.The results of this research show that the progress of the UHC (UniversalHealth Coverage) program in Semarang has been good in providing free services forresidents of Semarang. So that the goal for the welfare of society through health canbe achieved. The most profound obstacles are often mistargeted because thesocialization of the program gives less community awareness. And resources on thebudget when tuition rates rise certainly the number of budgets is getting bigger.Keywords: Health Program Evaluation, Universal Health Coverage Semarang